The robotic platform control with ATMEGA328 and NUTTYFI based on the Internet of Things - Gehlot, Anita; Singh, Rajesh (Electrical engineer); Sethi, Gaurav; Singh, Bhupendra (Robotics research and technology, internet theory, technology and applications, 2020)
"This book's aim is to explore the Robotic Platform Control with Atmega328 and NuttyFi based Internet of Things (IoT). IoT is network of networks and analytics system which exploits sensing, big data and artificial intelligence technology for complete system or service. IoT has applications across industries due to its unique flexibility and ability to be suitable in any environment. This book provides the basic knowledge of mobile apps with their design steps and programs. The objective of this book is to discuss the various methods to control the robotic platform where the Internet of Things plays an important role. This text is beneficial for people who want to get started with hardware-based robotics prototypes using the IoT. Mobile platform is one of the most popular devices. It is designed for sports robots (football, volleyball etc.), rescue operations (fire-fighting, person or object finding etc.) and many other uses. This book discusses the different components required in the design process of the robot"--